Analisis Kualitas Produk Dan Pelayanan Pada Tingkat Kepuasan Pelanggan Produk Karet Ribbed Smoked Sheet PT. Perkebunan Nusantara III (Persero) - Muhammad Adlin Panjaitan; Retna Astuti K; Harso Kardhinata (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2023)
Competition between companies is currently very tight, along with the development of science and technology. Consumers no longer buy products based solely on physical appearance, but also include all aspects of the service attached to the product. The purpose of this study was to determine the effect of product quality and service quality on customer satisfaction at PT PERKEBUNAN NUSANTARA III (PERSERO). The type of research used is associative research with the method of Multiple Linear Regression analysis. The results showed that product quality and service quality had a positive and significant effect on customer satisfaction at PT Perkebunan Nusantara III (PERSERO). This means that the product quality and service quality at PT Perkebunan Nusantara III are very good.